Multidisciplinary treatment of a fractured root: a case report - Cuoghi Osmar Aparecido; Bosco Álvaro Francisco; de Mendonça Marcos Rogério; Tondelli Pedro Marcelo; Miranda-Zamalloa Yésselin Margot (Sciendo, 2023)
To describe the orthodontic, periodontal and prosthetic management of a case with a 3 mm root fracture below the crest of the alveolar bone.